Драма і театр України 1940–1950 рр. - Барабан, Л. (Студії мистецтвознавчі, 2007)
The author analyses the most characterizing trends in the Ukrainian dramatic art in 1940–1950. He analyses specific features of Î. Kopylenko’s, V. Vasylko’s, I. Kocherha’s plays and plays of other Ukrainian playwrights.